Issues of modern family institution affected by media environment - V. Zotova, Marina (2021)
The objective of the paper consists in discussing the crisis of the modern institution of family, influence of the media environment on social and psychological condition of its users, as well as on family values forming in young people. In studying this problem, the leading method is analysis of Russian and foreign theoretical and practical materials dealing with the issue of young people's views shaping under the influence of the media environment. The analysis allows finding out inability of the young to wisely check incoming information flows and the adverse effect on value orientations and the image of family created. In the paper, the following principal results are presented. Young people's views on founding a family and identifying information sources which are preferable for them have been found out. The young have been analyzed as the object of action of the media environment. Materials of the paper can be of help for young people, specialists working with the young, and parents in using mass media consciously. They can also be instrumental in developing specialized programs for forming young people's image of family and value orientations as free from the media influence.